Socio-Economic Effectiveness of the Development of the Railway Network in Siberia and the Far East: Mathematical Simulation and Forecast - Sadovnichii, Viktor Antonovich; Osipov, Gennady Vasilyevich; Akaev, Askar Akaevich; Malkov, Artemy Sergeevich; Shuigin, Sergey Georgievich (Economy of Regions, 2018)
The purpose of the research consists in the quantitative evaluation of long-term macroeconomic, social, geopolitical effects from the realization of the project of the development of the railway network in Siberia and the Far East, including the building of high-speed rail. In the study, we applied the methods of mathematical simulation and forecasting. Calculations with the use of the developed mathematical models have shown that the implementation of this project will play a large role in the socio-economic development of the country as well as in strengthening its geo-economic and geopolitical positions in the Asia-Pacific Region and in the world as a whole.